Search for supersymmetry with photons in pp collisions at root s=8 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2015)
Two searches for physics beyond the standard model in events containing photons are presented. The data sample used corresponds to an integrated luminosity of 19.7 fb(-1) of proton-proton collisions at root s = 8 TeV, collected with the CMS experiment at the CERN LHC. The analyses pursue different inclusive search strategies. One analysis requires at least one photon, at least two jets, and a large amount of transverse momentum imbalance, while the other selects events with at least two photons and at least one jet, and uses the razor variables to search for signal events. The background expected from standard model processes is evaluated mainly from data. The results are interpreted in the context of general gauge-mediated supersymmetry, with the next-to-lightest supersymmetric particle either a bino- or wino-like neutralino, and within simplified model scenarios. Upper limits at the 95% confidence level are obtained for cross sections as functions of the masses of the intermediate supersymmetric particles.
Keywords: PARTON DISTRIBUTIONS; BREAKING; MODELS; SQUARK